Beyond Cervical Length: Association between Postcerclage Transvaginal Ultrasound Parameters and Preterm Birth - Battarbee, Ashley N.; Ellis, Joshua S.; Manuck, Tracy A. (American Journal of Perinatology, 2019)
Objective To assess the value of transvaginal ultrasound parameters after cerclage placement in estimating the risk of spontaneous preterm birth.Study Design This is a retrospective cohort at a single tertiary care center from 2013 to 2016. Women carrying a singleton, nonanomalous fetus with cerclage in situ and at least one postcerclage transvaginal ultrasound from 160/7 to 256/7 weeks' gestation were included. In addition to abstracting maternal demographic and obstetric characteristics, two study investigators separately reviewed each of the images from the first transvaginal ultrasound after cerclage placement, masked to pregnancy outcomes. We measured the angle between the anterior uterine wall and cervical canal at the internal os and external os, closed canal length above and below the stitch, width of the anterior and posterior cervix at the level of the cerclage, and stitch distance from the cervical canal. The presence of additional ultrasound findings such as sludge and cervical funneling was also noted. The main outcomes were preterm birth < 34 weeks and preterm birth < 37 weeks. Transvaginal ultrasound parameters were compared between women with preterm birth and those without preterm birth using chi-square, Fisher's exact, and Wilcoxon's rank-sum tests, as appropriate. Log binomial regression was used to estimate the relative risk of preterm birth for all significant obstetric and ultrasound characteristics.Results A total of 102 women met inclusion criteria: 58% had history-indicated, 20% ultrasound-indicated, and 23% exam-indicated cerclages. Of these, 28 (27.5%) women delivered at < 34 weeks' gestation, and 48 (47.0%) women delivered at < 37 weeks' gestation. Preterm birth did not vary by race, maternal age, insurance, smoking, or gestational age of the earliest prior preterm birth (for multiparous women), but women who had preterm birth were more likely to have exam-indicated cerclage. There were several transvaginal ultrasound parameters associated with preterm birth < 34 weeks and preterm birth < 37 weeks. Of these, cervical length below the stitch, stitch distance from the cervical canal, straight cervical canal, funneling to or past the stitch, and presence of sludge had the greatest effect sizes.Conclusion Rates of preterm birth are high postcerclage. In addition to measuring cervical length, utilization of postcerclage transvaginal ultrasound to evaluate the location of the cerclage within the cervix, the curvature of the cervical canal, and the presence of funneling and sludge may help identify women who are at the highest risk for preterm birth.
Keywords: cerclage; cervical length; preterm birth; ultrasound; uterocervical angle